Orbiniidae (Annelida: Errantia) from Lizard Island, Great Barrier Reef, Australia with notes on orbiniid phylogeny - Zhadan, Anna; Stupnikova, Alexandra; Neretina, Tatiana (Zootaxa, 2015)
The fauna of Orbiniidae (Annelida: Errantia) from the Lizard Island has been studied. Five species were found and each was redescribed and illustrated using light microscopy and SEM. Scoloplos acutissimus Hartmann-Schröder, 1991 and Scoloplos dayi Hartmann-Schröder, 1980 collected for the first time since their original descriptions and confirmed through re-examination of their type materials. Molecular analyses were carried out using nuclear 18S rDNA and mitochondrial 16S rDNA and CO1 gene sequences with evolutionary distances and the Neighbor-Joining Method. The molecular analyses did not support the monophyly of the genera Scoloplos, Leitoscoloplos, Leodamas, and Naineris, and its results are incongruent with morphological data.